CSF neopterin level as a diagnostic marker in primary central nervous system lymphoma. Issue 11 (25th May 2015) - Viaccoz, Aurélien; Ducray, François; Tholance, Yannick; Barcelos, Gleicy Keli; Thomas-Maisonneuve, Laure; Ghesquières, Hervé; Meyronet, David; Quadrio, Isabelle; Cartalat-Carel, Stéphanie; Louis-Tisserand, Guy; Jouanneau, Emmanuel; Guyotat, Jacques; et al.
Abstract: Background: The diagnosis of primary central nervous system lymphoma (PCNSL) can be challenging. PCNSL lesions are frequently located deep within the brain, and performing a cerebral biopsy is not always feasible. The aim of this study was to investigate the diagnostic value of CSF neopterin, a marker of neuroinflammation, in immunocompetent patients with suspected PCNSL. Methods: We retrospectively reviewed the characteristics of 124 patients with brain tumor ( n = 82) or an inflammatory CNS disorder ( n = 42) in whom CSF neopterin levels were assessed. Twenty-eight patients had PCNSL, 54 patients had another type of brain tumor (glioma n = 36, metastasis n = 13, other n = 5), and 13 patients had a pseudotumoral inflammatory brain lesion. Results: CSF neopterin levels were significantly higher in the patients with PCNSL than in those with other brain tumors (41.8 vs 5.1 nmol/L, P < .001), those with pseudotumoral inflammatory brain lesions (41.8 vs 4.3 nmol/L, P < .001), and those with nontumefactive inflammatory CNS disorders (41.8 vs 3.8 nmol/L, P < .001). In the 95 patients with space-occupying brain lesions, at a cutoff of 10 nmol/L, the sensitivity of this approach was 96% and the specificity was 93% for the diagnosis of PCNSL. The positive and negative predictive values were 84% and 98%, respectively. Conclusion: Assessing CSF neopterin levels in patients with a suspected brain tumor might be helpful for the positive and differential diagnosis of PCNSL. A prospective study is warranted to confirm these results.